The spatial Matryoshka doll: New perspectives on the settlement dynamic of the Kura-Araxes - Batiuk, Stephen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Investigations into the Kura-Araxes have significantly accelerated over the past two decades, of which Ruben Badalyan has been a leading figure. Of particular interest is the spread of the Kura-Araxes sites across a large portion of the Near East, whose number has significantly grown over the past two decades due to the increase of surveys in the Middle East and Caucasia. While many have focused on the meaning of this increase in settlement vis-à-vis migration, trade or cultural assimilation, few have delved stratigraphically into the data like Badalyan to look for patterns to illuminate our understandings of the Kura-Araxes. This paper represents a preliminary examination of the newer larger database of Kura-Araxes settlement, exploring the intersection between various spatial and environmental contexts, and what it might mean to our understandings of the Kura-Araxes.